Myasthenia gravis patient and physician opinions about immunosuppressant reduction. Issue 6 (20th March 2020) - Hehir, Michael K.; Punga, Anna Rostedt; Ciafaloni, Emma
Abstract: Introduction: To reduce myasthenia gravis (MG) patient risk of immunosuppressant (IS) exposure adverse events (AEs), such as infections and malignancies, and to reduce treatment burden, international guidelines recommend decreasing IS dose in stable MG patients. Methods: Online surveys were conducted of self‐identified MG patients and MG physician experts about the importance of IS dose reduction for MG patients who achieve prolonged periods of disease stability. Results: Eighty‐four percent of MG patients (n = 283) and 100% of physicians (n = 45) were concerned about long‐term IS‐associated AEs. Although both groups favored attempting IS reduction, they raised concerns including MG relapse, hospitalization, and uncertainty about the future. Presented with an estimated 12% significant relapse rate with IS dose reduction, 76% of patients would be willing to enroll in a randomized IS dose reduction trial. Discussion: Patients and physicians favor considering IS dose reduction but are also concerned about potential negative sequelae.